Efektivitas Layanan Informasi Bahaya Bermain Game Online menggunakan Media Flipchart dalam Mengurangi Intensitas Bermain Game Online Disekolah Siswa Kelas VII SMP Negeri 3 Setukabupaten Bekasi - Iwan Riswandi; Tatag Mulyanto (Malahayati Nursing Journal, 2024)
ABSTRACT Education comes from the basic word didik. In Indonesian Dictionary, the word didik is defined as the process of "maintaining and giving training (teachings, guidance, guidance) regarding morals and intelligence of the mind. Knowing the Effectiveness of Information Services through flipchart media in reducing the intensity of playing online games. Quasy experimental research with a two-group pre-post test research design with a sample of 52 students. The results of the descriptive analysis showed that the intensity of playing online games before being given information services on the dangers of playing online games was 33 or 63.5% who had a very high intensity of playing online games, 12 or 23% of students who had a high intensity of playing online games, 3 or 5.8% of students who had a moderate intensity of playing online games, and 4 or 7.7% of students who had a very low intensity of playing online games,  While after being given information services on the dangers of playing online games, there was a reduction of 9 or 17.3% who had a very high intensity of playing online games, there were 10 or 19.2% of students who had a high intensity of playing online games, there were 27 or 52% of students who had a moderate intensity of playing online games, and there were 6 or 11.5% of students who had a very low intensity of playing online games. Based on the results of the study proved that information services on the dangers of playing online games accompanied by flipchart media are effective in reducing the intensity of playing online games. Keywords: Online Game, Flipchart Media, Intensity of Playing Online Games.  ABSTRAK Pendidikan berasal dari kata dasar didik. Dalam Kamus Bahasa Indonesia, kata didik didefinisikan sebagai proses “memelihara dan memberi latihan (ajaran, tuntunan, pimpinan) mengenai akhlak dan kecerdasan pikiran. Mengetahui Efektifitas Layanan informasi melalui media flipchart dalam mengurangi intensitas bermain game online. Penelitian pra-eksperimental-semu (quasy experimental research) dengan desain penelitian pre-post test dua kelompok dengan sampel 52 siswa. Hasil analisis deskriptif menunjukan bahwa intensitas bermain game online sebelum diberikan layanan informasi bahaya bermain game online yaitu 33 atau 63,5 % yang memiliki intensitas bermain game online sangat tinggi, 12 atau 23 % siswa siswa yang memiliki intensitas bermain game online tinggi, 3 atau 5,8% siswa yang memiliki intensitas bermain game online sedang, dan 4 atau 7,7 % siswa yang memiliki intensitas bermain game online sangat rendah, sedangkan sesudah diberikan layanan informasi bahaya bermain game online maka terjadi pengurangan yaitu 9 atau 17,3 % yang memiliki intensitas bermain game online sangat tinggi, ada 10 atau 19,2 % siswa yang memiliki intensitas bermain game online tinggi, ada 27 atau 52 % siswa yang memiliki intensitas bermain game online sedang, dan ada 6 atau 11,5 % siswa yang memiliki intensitas bermain game online sangat rendah. Berdasarkan hasil penelitian membuktikan bahwa layanan informasi bahaya bermain game online disertai media flipchart efektif dalam mengurangi intensitas bermain game online. Kata Kunci: Game Online, Media Flipchart, Intensitas Bermain Game Online.